2010
DOI: 10.4111/kju.2010.51.4.257
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Asymptomatic Urethral Caruncle on Micturition in Women with Urinary Incontinence

Abstract: PurposeThe aim of this study was to evaluate the effect of asymptomatic urethral caruncle (UC) on micturition in women suffering from urinary incontinence.Materials and MethodsA total of 232 patients participated in the study. UC was diagnosed in 50 of 232 patients with urinary incontinence during a physical examination in our clinic. All cases were divided into 2 groups: UC combined with urinary incontinence (group 1) and urinary incontinence only (group 2). Urodynamic evaluations were performed according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…After almost three centuries of identification, its etiopathogenesis is still not fully illuminated. Many factors such as recurrent infections, chronic irritation, estrogen insufficiency and chronic inflammatory diseases with chronic granulation tissue formation are blamed for its etiology 4,9 . Histologically, urethral caruncles could have papillomatous, angiomatous or granulomatous morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After almost three centuries of identification, its etiopathogenesis is still not fully illuminated. Many factors such as recurrent infections, chronic irritation, estrogen insufficiency and chronic inflammatory diseases with chronic granulation tissue formation are blamed for its etiology 4,9 . Histologically, urethral caruncles could have papillomatous, angiomatous or granulomatous morphology.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hyperplastic areas could be observed on the surface epithelium. However, it could also be observed that the surface epithelium forms cystic or glandular structures as a result of its invagination into sub-epithelium stromal areas 9,10 . Previous studies mentioned that malignancy could be encountered postoperatively, albeit rarely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pain, and dysuria may occur and few patients may seek consultation for bleeding from the lesion after noticing staining of undergarments. Urinary retention has been reported but storage or voiding abnormalities are not observed in urodynamic studies [4]. Tumors occur in about 2% of urethral caruncles and intraepithelial squamous cell carcinoma has been reported arising within the urethral caruncle [5].…”
mentioning
confidence: 99%